Developing A Digital Model As A Literature For Preventing And Overcoming Cyberbullying Among Children And Teenagers K-Pop Fans - Anwar, Citra Rosalyn; Arnidah, Arnidah; Lidayni, Asnur (Journal of Educational Science and Technology (EST), 2023)
This study aimed to develop a digital module for Digital Literacy for children and young people who were KPop fans in Makassar, to prevent cyberbullying. Data showed that that K-Pop fans consisting of children and teenagers in Indonesia were one of the largest Internet users in the world. The high use of the internet was also directly proportional to the cyberbullying that occured to them, not only as victims but also as perpetrators. This was the reason, why this study was important to investigate even though many researches on digital literacy had been carried out, but not many had been found specifically targeting KPop fans, while they were active internet users. This study was development research referring to the 4-D model (Four) that proposed by S. Thiagarajan and Semmel (1974), which consisted of 4 stages of development, namely the stage of defining (Define), Design , Development (Develop), and dissemination (Disseminate), then reduced to a 3-D model which only consisted of 3 stages of development, namely the stage of defining (Define), Design, Development (Develop). The results produced a Digital Literacy Module, which emphasized content on digital skills, consisting of Devices used, Search Engines, social media applications and online conversations and shopping, all of which were adapted to the characteristics of KPop Fans.